Dentist’s clinical conduct facing the avulsion of deciduous and permanent teeth: integrative review (Brazilian Journal of Health Research, 2022)
Introduction: Tooth avulsion is one of the most serious traumatic dental injuries, affecting mainly children and adolescents. Therefore, it is necessary that the dentist has suficient knowledge about the conduct taken in the face of this problem. Objectives: To evaluate available scientific evidence regarding clinical management of avulsed deciduous and permanent teeth by the dentist. Methods: This is an integrative review, in which a systematic literature search was conducted in Lilacs, Scielo, Bireme and Pubmed databases, using independently the following descriptors in Portuguese and English: Tooth Avulsion (Avusão Dentária), Tooth Replantation (Reimplante Dentário) and Tooth Trauma (Traumatismo Dentário). Selection criteria were applied to titles, abstracts and full texts. Articles published in Portuguese, Spanish and English between 2005 and 2020 were selected. The articles were analyzed regarding the procedures that must be performed in cases of tooth avulsion and categorized according to the dentition. Results: 27 articles were included. There was agreement regarding clinical conduct among studies. In primary dentition, dental replantation is not recommended. It is important to maintain the space created and to monitor the successor permanent tooth. While it is recommended in permanent dentition in order to prolong tooth socket time and improve patient’s self-esteem. Conclusion: Knowledge about the clinical conduct of dental avulsion by the dentist is essential for the proposed procedures. Besides that, it might minimize the impact of these injuries on children and adolescents.
Keywords: Tooth Avulsion; Tooth Replantation; Tooth Injuries